2021
DOI: 10.3389/fimmu.2021.732938
|View full text |Cite
|
Sign up to set email alerts
|

Computational Construction of a Single-Chain Bi-Paratopic Antibody Allosterically Inhibiting TCR-Staphylococcal Enterotoxin B Binding

Abstract: Staphylococcal enterotoxin B (SEB) simultaneously crosslinks MHC class II antigen and TCR, promoting proliferation of T cells and releasing a large number of toxic cytokines. In this report, we computationally examined the possibility of using a single-chain biparatopic bispecific antibody to target SEB and prevent TCR binding. The design was inspired by the observation that mixing two anti-SEB antibodies 14G8 and 6D3 can block SEB-TCR activation, and we used 14G8-6D3-SEB tertiary crystal structure as a templa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Our previous work [ 14 ] indicated that the communication between antibody and antigen could be reflected in the amino acid residue covariance matrix, which measures the motion correlations between any two residues in a protein complex. Figure 5 compares the covariance matrixes for the antibody–TRBC system with higher affinities (upper panel) and lower affinities (lower panel).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous work [ 14 ] indicated that the communication between antibody and antigen could be reflected in the amino acid residue covariance matrix, which measures the motion correlations between any two residues in a protein complex. Figure 5 compares the covariance matrixes for the antibody–TRBC system with higher affinities (upper panel) and lower affinities (lower panel).…”
Section: Resultsmentioning
confidence: 99%
“…This model is trained on SKEMPI [27] Antibody-Bind (AB-Bind) [28] datasets, both curated antibody-antigen complexes with single-site and multi-site mutations and corresponding free energy change values (∆∆G). The training dataset comprises Computational antibody designs have been developed to help antibody designs [10][11][12][13][14][15][16], including molecular mechanical energy-based de novo design [11], molecular dynamics simulations [14,[17][18][19], structure-based antibody prediction and similarity measure of antibody-antigen interfaces [20,21]. Molecular docking and subsequent MD simulation have also been used to predict the binding mode of JOVI-1 with TRBC1 [19].…”
Section: Ai Model Training and Prediction Of Antibody-antigen Binding...mentioning
confidence: 99%
See 2 more Smart Citations
“…Heat-labile toxins expressed by E. coli and Vibrio cholerae lead to apoptosis or elimination in T cells ( 36 ). Superantigens, represented by staphylococcal enterotoxins, could induce a non-antigen-specific activation of T cells by cross-linking MHC and TCR with the presence of APCs, leading to rapid proliferation and release of cytokines ( 37 , 38 ). Our results suggested a potential risk raised by co-exposure of enterotoxins and food allergens.…”
Section: Discussionmentioning
confidence: 99%